Factors related to post-stroke depression during the first 2 weeks after stroke. (January 2021) - Mitsunaga, Wataru; Higashi, Toshio; Moriuchi, Takefumi; Koyanagi, Masahiko; Honda, Yuuichirou; Okita, Minoru; Honda, Sumihisa; Tateishi, Youhei; Shiraishi, Hirokazu; Tsujino, Akira
Introduction: This study aimed to clarify factors associated with post-stroke depression in patients with acute stroke within 2 weeks of onset. Method: Eighty-eight patients with stroke were divided into post-stroke depression ( n  = 49) and non-post-stroke depression ( n  = 39) groups based on their Hamilton Depression Rating Scale scores. We evaluated stroke severity, upper limb function, activities of daily living, frontal lobe/cognitive function, and level of apathy. Activity levels were measured using an ActiGraph GT9X Link system. Mann–Whitney U -tests were used to determine differences between the two groups. Spearman's rank correlation and logistic regression analyses were also performed. Results: The post-stroke depression and non-post-stroke depression groups exhibited significant differences in National Institutes of Health Stroke Scale scores at admission and discharge; Functional Independence Measure exercise items, cognitive items, and total items at admission; Fugl-Meyer Assessment scores; and Apathy Rating Scale scores. Logistic regression indicated that Fugl-Meyer Assessment scores were associated with post-stroke depression. Conclusion: Stroke severity, paralysis, and physical function/activities of daily living ability are associated with post-stroke depression in the acute phase. Our findings suggest that increases in physical impairment severity are associated with increased post-stroke depression risks. Rehabilitation professionals should focus on identifying post-stroke depression in early post-stroke stages.